Método de avaliação visual aplicado ao recém-nascido - Lúcio, Ingrid Martins Leite (2004)
This is a quantitative study, which took place in a public maternity of Fortaleza - CE during the months of March and May of 2004. The aim was to describe the implementation of a visual evaluation during the intern of 114 premature newborns (PN) whose gestation age until birth was under 37 weeks. The babies’ mothers gave their permission to be subject of the study. The evaluation questionnaire consisted of three categories: 1) maternal and newborn history, 2) ocular exam and 3) nursing care. The data was analysed with the help of SPSS software 11.0 version and presented through table charts. To analyse the 2x2 tables it was used Fisher’s tests and for the rxc tables, Fisher-Freeman-Halton’s tests, adopting a significance level of 5%. Under the category maternal history, the data showed that the age’s ratio of the mothers was 23 and 3.8 was the average number of pre - natal consultation. Under family history/ophthalmologic, it stood out deflection errors (17%) followed by diabetes (14%) and in a lower frequency, cataract (4%) and glaucoma (1%). Under personal history it stood out high blood pressure (12%) followed by visual disorder (8%). Under newborn history it was found that 71% of PN were born thought caesarean section, also 52% are female and 68% had an apgar lower than seven during the first minute of their lives. 78% were average PN according to the premature classification. It was found that 112 PN used oxigenotherapy in which 71% of them were between the ages of 1 and 10 days. Also 68 PN were under phototherapy in which 53% were between 1 and 5 days old. The prophylaxis against newborn ophthalmologic disease was done in 27% of the premature newborns. As for the external ocular exam, 27% of those babies showed alteration in the eyelid, 16% in the conjunctiva, 14% in the sclera, 9% in the lachrymal duct, 6% in the cornea and 5% in the pupil (opening of the iris). None of the premature newborns showed any alterations on the eyebrow or iris. There was a meaning variation between the sclera and the ophthalmologic medication used (p=0,055). Thirteen premature newborns (11%) showed variation of the extra-ocular movements (physiologic strabismus) and thirteen (11%) had their red reflex altered. It was found a relevant relation among the red reflex, the apgar in the first minute of the newborns’ lives (p=0,041) and the time of oxigenotherapy treatment (p=0,028). The nursing care, based on visual assessment, was noted on the register book, informed to the nursing team, conducted as an specific treatment for the newborns’ vision, transmitted to their parents and other professionals (if one was to be needed). The results showed that the method used was efficient because it emphasizes and identifies factors that may help cooperate treatments against premature visual disorders. Indeed a technology resource contributes to the knowledge and nursing practice for the newborns’ visual health. The evaluation process came to be useful and necessary during a newborn intern period as one of the nursing treatments to reduce children’s ocular disorders.